Application of Self and Peer Assessment with Feedback To Improve Control Concepts and Habits of Mind Students On Acid Titration Materials Bases - M Fikri Fahrurozi; Nahadi Nahadi; Hernani Hernani (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to apply self and peer assessment with feedback to improve the mastery of concepts and habits of mind students on the topic of acid-base titration. Selfassessment is an assessment carried out by ourselves on the progress achieved through the workings, while peer assessment visits of the ability of an individual to contribute to the task group. The method uses a quasi-experimental study with a non-equivalent pretest-posttest control group design. The instrument used to collect research data is the format of self and peer assessment, a matter of mastering the concept of acid-base titration, habits of mind questionnaire, interview and questionnaire responses sisiwa. Tests mastery of the concept of acid-base titration validated by 5 experts in the field of chemistry and formed a CVR index (Content Validity Ratio) between 0.60 to 1.00. Reliability tests mastery of the concept of acidbase titration test involving 60 respondents XI MIA 4 and 5 Senior High School and processed using SPSS 22.0 produce the coefficient value of 0.75 (included in the high criteria). Further research will be done self and peer assessment with feedback to improve the mastery of concepts and habits of mind students.